Intraoperative Ultrasound-Guided Excision of Non-Palpable and Palpable Breast Cancer: Systematic Review and Meta-Analysis - Banys-Paluchowski, Maggie; Rubio, Isabel T.; Karadeniz Cakmak, Güldeniz; Esgueva, Antonio; Krawczyk, Natalia; Paluchowski, Peter; Gruber, Ines; Marx, Mario; Brucker, Sara Y; Bündgen, Nana; Kühn, Thorsten; Rody, Achim; Hanker, Lars; Hahn, Markus (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Wire-guided localization (WGL) is the most frequently used localization technique in non-palpable breast cancer (BC). However, low negative margin rates, patient discomfort, and the possibility of wire dislocation have been discussed as potential disadvantages, and re-operation due to positive margins may increase relapse risk. Intraoperative ultrasound (IOUS)-guided excision allows direct visualization of the lesion and the resection volume and reduces positive margins in palpable and non-palpable tumors. We performed a systematic review on IOUS in breast cancer and 2 meta-analyses of randomized clinical trials (RCTs). In non-palpable BC, 3 RCTs have shown higher negative margin rates in the IOUS arm compared to WGL. Meta-analysis confirmed a significant difference between IOUS and WGL in terms of positive margins favoring IOUS (risk ratio 4.34, p < 0.0001, I2 = 0%). 41 cohort studies including 3291 patients were identified, of which most reported higher negative margin and lower re-operation rates if IOUS was used. In palpable BC, IOUS was compared to palpation-guided excision in 3 RCTs. Meta-analysis showed significantly higher rates of positive margins in the palpation arm (risk ratio 2.84, p = 0.0047, I2 = 0%). In 13 cohort studies including 942 patients with palpable BC, negative margin rates were higher if IOUS was used, and tissue volumes were higher in palpation-guided cohorts in most studies. IOUS is a safe noninvasive technique for the localization of sonographically visible tumors that significantly improves margin rates in palpable and non-palpable BC. Surgeons should be encouraged to acquire ultrasound skills and participate in breast ultrasound training.
Keywords: breast cancer; intraoperative ultrasound; wire-guided localization; resection margins; reoperation rate